Determining Sustainability Growth: Analysis of Dividend Policy, Capital Structure, Liquidity, and Financial Statement Digitalization Mediated by Profitability - Ni Nyoman sawitri; Idel Eprianto (Greenation International Journal of Economics and Accounting, 2025)
The purpose of this literature review is to develop hypotheses for future authors conducting research related to sustainability growth. The research article Determination of Sustainability Growth: Analysis of Dividend Policy, Capital Structure, Liquidity, and Digitalization of Financial Statements Mediated by Profitability is a scientific literature article in the field of financial management. The approach used in this literature review is descriptive qualitative. The data collection technique involves conducting a literature review or reviewing relevant previous articles. The data used in this study are secondary data with a maximum publication age of 8 years, sourced from academic online media such as Thomson Reuters Journals, Sage, Springer, Taylor & Francis, Scopus Q2-Q4 Emerald, Elsevier, Sage, Springer, Web of Science, Sinta 2-5 Journals, DOAJ, EBSCO, Google Scholar, and digital reference books. Empirical data was used to support the phenomena observed in this study. In this study, one relevant previous study was used for each topic to review the research findings. The results of the literature review are as follows: 1) Dividend policy affects profitability; 2) Capital structure affects profitability; 3) Liquidity affects profitability; 4) Financial statement digitization affects profitability; 5) Dividend policy affects sustainability growth; 6) Capital structure affects sustainability growth; 7) Liquidity affects sustainability growth; 8) Financial statement digitization affects sustainability growth; 9) Profitability affects sustainability growth; 10) Dividend policy affects sustainability growth through profitability; 11) Capital structure affects sustainability growth through profitability; 12) Liquidity affects sustainability growth through profitability; and 13) Financial statement digitization affects sustainability growth through profitability.